Advances in the study of traditional Chinese medicine affecting bone metabolism through modulation of oxidative stress - Li, Jiaying; Cao, Hong; Zhou, Xuchang; Guo, Jianmin; Zheng, Chengqiang (Frontiers in Pharmacology, 2023)
Bone metabolic homeostasis is dependent on coupled bone formation dominated by osteoblasts and bone resorption dominated by osteoclasts, which is a process of dynamic balance between bone formation and bone resorption. Notably, the formation of bone relies on the development of bone vasculature. Previous studies have shown that oxidative stress caused by disturbances in the antioxidant system of the whole organism is an important factor affecting bone metabolism. The increase in intracellular reactive oxygen species can lead to disturbances in bone metabolism, which can initiate multiple bone diseases, such as osteoporosis and osteoarthritis. Traditional Chinese medicine is considered to be an effective antioxidant. Cumulative evidence shows that the traditional Chinese medicine can alleviate oxidative stress-mediated bone metabolic disorders by modulating multiple signaling pathways, such as Nrf2/HO-1 signaling, PI3K/Akt signaling, Wnt/β-catenin signaling, NF-κB signaling, and MAPK signaling. In this paper, the potential mechanisms of traditional Chinese medicine to regulate bone me-tabolism through oxidative stress is summarized to provide direction and theoretical basis for future research related to the treatment of bone diseases with traditional Chinese medicine.